Creeping Marketization: Where Polish Public and Private Higher Education Sectors Meet. - Kwiek, Marek (My University, 2011)
This chapter discusses changes in Polish higher education related to marketization. The wider context is the transition from a command-driven, communist economy to a market-driven, op en economy and from a communist authoritarian bureaucracy to a parliamentary democracy. The chapter discusses funding mechanisms with respect to institutions, teaching and research; distinct processes marking the turn toward marketization—increasing financial self -reliance of academic institutions and external privatization (growth in the number of private sector providers) and internal privatization (finance-driven cost-recovery mechanisms in public sector institutions). Finally, the chapter discusses market forces in the context of Polish educational policies and offers some concluding remarks.
Keywords: higher education; Poland; privatization; private sector; public-private dynamics; Central and Eastern Europe; massification; Polish universities; cost-sharing; tuition fees; independent private sector; marketization; funding mechanisms; university funding; postcommunist transition; public policy; state and market